Teorías de la Justicia y de la Legitimación: Una reivindicación de la sustantividad en las Teorías de la Justicia - Vanney, María Alejandra (Revista de Derecho, 2019)
This article discusses a general class of theories that attempt to base a normative account of justice on consent-giving procedures. Contemporary political philosophers offer many different accounts of justice, but at present consent-based theories are probably the most popular. Notwithstanding their (often understandable) appeal, I will argue they cannot possibly succeed. All consent-based theories trade on a crucial ambiguity as to whether they are supposed to be understood as voluntarist accounts of justice on the one hand, or as rationalist accounts on the other. In the formercase, consent-based theories fail because they are at best indeterminate and at worst incoherent; in the latter case, they fail because they are superfluous. I will refer to this fatal ambiguity as “Cassirer’s Dilemma.” Interestingly, Cassirer’s Dilemma is not at all new, on the contrary, it may be among the oldest problems plaguing western moral and political philosophy. Faced with this insurmountable difﬁculty, I believe we ought to abandon proceduralism and focus instead on developing substantive accounts of justice